ON THE BIOMETRY, FOOD AND FEEDING AND SPAWNING HABITS OF OTOLITHES RUBER (SCHNEIDER) FROM PORTO NOVO - Pillai, P K Mahadevan (Indian Journal of Fisheries, 2011)
Out of the 17 morphometric characters studied, the distance between the tip of snout and insertion of anal fin was observed to have the fastest growth rate in Otolithes ruber (Schneider) along the Porto Novo coast. O. ruber, highly carnivorous, shows a selectivity of feeding. The ova-diameter frequency suggests that spawning takes place in O. ruber only once a season, for a shoh duration